COMPARATIVE ANALYSIS OF PHYTOCHEMICALS IN ACACIA CATECHU BARK EXTRACTS FROM GUNA DISTRICT, MADHYA PRADESH - TIWARI, ARCHANA; TIWARI, AVINASH (International Journal of Current Pharmaceutical Research, 2024)
Objective: Current study aims to discover novel sources of physiologically active natural chemicals with diverse applications. In this study, four types of specific phytochemical in different extracts of Acacia catechu bark samples were investigated, which were collected from. Additionally, bibliographic analysis was conducted using dimensions research database. Methods: For this phytochemical screening, some common and standard test methods were done. Qualitative test for Phenols was done using Lead acetate test method; proteins were quantified by biuret and ninhydrin method, carbohydrates by Molish test, benedict’s test and Fehling’s test, and starch by using Iodine test method. Results: Phytochemical screening showed the phenolic compounds (different colour intensity in different samples) and soluble carbohydrates (almost same colour intensity in all test samples) are present and both proteins and insoluble carbohydrate (starch) are completely absent in all test extracts. Conclusion: The bibliographic analysis indicated the therapeutic values as well as the unavailability of published studies with these special parameters. This preliminary study provide base to find out the possible medicinal significance of Acacia catechu of Guna district and also serve as the base for further investigations.